Establishment of sterilization procedures in in vitro culture for node of dukung anak (Phyllanthus niruri L.) - Mohd Saleh, Kamsiah (2015)
An experiment was conducted to determine the best sterilization procedure for in vitro culture of dukung anak (Phyllanthus niruri Linn) using node explant. Different concentrations of Clorox at different immersion time were used to optimise the sterilization procedure. Using 15% (2X) concentration of Clorox with 10 minutes immersion time a decrease in percentage of contamination was observed compared to the other treatment. In another experiment the best sterilisation treatment from previous experiment was used to sterilise Phyllanthus niruri node explant. After sterilisation this explant was inoculated in MS medium supplemented with different plant preservative mixture (PPM) concentration. Addition of 2 ml/L PPM into the MS media resulted in a high survival percentage (75%) of node explant while reducing the fungal contamination to 6.7%. Despite that, the contamination percentage by bacteria still exists. Further studies need to be carried out to obtain 100% contamination free explants while increasing its survival percentage.